Penyuluhan tentang Pentingnya Menjaga Protokol Kesehatan pada Masa Pandemi di Panti Asuhan Al-Kaaf Jabung Kabupaten Malang - Fitri; Herman Hariyadi; Lucky Nindya Palupi; Muhammad Khairuddin; Leonardo Kamajaya (P3M Politeknik Negeri Malang, 2022)
The implementation of counseling about the importance of health protocols during the pandemic was carried out at the Al-Kaaf Jabung Orphanage, Malang Regency. The equipment used is a laptop, hand sanitizer, masks, and soap for washing hands. The method of this counseling is the tutorial through the zoom meeting application, followed by the students and orphanage administrators, because it is still in the pandemic period. The speakers in this activity are the teaching staff of the Electrical Engineering Department, State Polytechnic of Malang who in this case are members of this PkM activity and are assisted by students of State Polytechnic of Malang. The results of this dedication, it is hoped that the participants apply 5M in their daily life so that they can break the chain of the spread of COVID-19.